A systematic review and meta‐analysis of utility estimates in melanoma. (1st February 2018) - Tran, A.D.; Fogarty, G.; Nowak, A.K.; Espinoza, D.; Rowbotham, N.; Stockler, M.R.; Morton, R.L.
Summary: Background: Health‐related quality of life (HRQOL) in melanoma is affected by cancer stage. Previous studies have reported limited data on utility‐based HRQOL. Objectives: To determine pooled estimates of utility‐based HRQOL (utilities) for people with American Joint Cancer Committee stage I/II, III or IV melanoma for use in economic evaluations. Methods: We performed a systematic review, meta‐analysis and metaregression of utilities for patients with melanoma. HRQOL scores reported with the QLQ‐C30, SF‐36, SF‐12, FACT‐G and FACT‐M instruments were converted to utilities using published mapping algorithms. Meta‐analysis was used to calculate mean utilities. Metaregression was used to examine the effects of baseline patient and study characteristics. Results: We identified 33 studies reporting 213 utilities. From meta‐analyses, the mean utility for stage I/II melanoma was 0·97 [95% confidence interval (CI) 0·90–0·98]; for stage III melanoma it was 0·77 (95% CI 0·70–0·83); for stage III/IV 0·76 (95% CI 0·76–0·77); and for stage IV melanoma 0·76 (95% CI 0·71–0·81). The difference in utility between stage III and stage IV was not statistically significant ( P = 0·52). For patients with stage I/II, the utility estimate at the time of surgery was 0·77 (95% CI 0·75–0·79), and at 3–12 months postsurgery it was 0·85 (95% CI 0·84–0·86). Utility estimates for patients with stage IV melanoma were 0·65 (95% CI 0·62–0·69) during the first 3 months of treatment and 0·83 (95% CI 0·81–0·86) at 4–12 months on treatment. For patients with stage IV melanoma treated with chemotherapy, the utility estimate was 0·52 (95% CI 0·51–0·52), while for those treated with targeted therapy it was 0·83 (95% CI 0·82–0·85). Conclusions: These robust, evidence‐based estimates of health state utility can be used in economic evaluations of new treatments for patients with early‐stage or advanced‐stage melanoma.